Characterization of the chicken melanocortin 5 receptor and its potential role in regulating hepatic glucolipid metabolism - Zhang, Xiao; Su, Jiancheng; Huang, Tianjiao; Wang, Xinglong; Wu, Chenlei; Li, Jing; Li, Juan; Zhang, Jiannan; Wang, Yajun (Frontiers in Physiology, 2022)
Melanocortin receptors (MC1R-MC5R) and their accessory proteins (MRAPs) are involved in a variety of physiological processes, including pigmentation, lipolysis, adrenal steroidogenesis, and immunology. However, the physiological roles of MC5R are rarely characterized in vertebrates, particularly in birds. In this work, we cloned the full-length cDNA of chicken MC5R and identified its core promoter region. Functional studies revealed that cMC5R was more sensitive to ACTH/α-MSH than β-MSH/γ-MSH, and was coupled to the cAMP/PKA signaling pathway. We demonstrated that MRAP2 decreased MC5R sensitivity to α-MSH, whereas MRAP1 did not have a similar effect, and that both MRAPs significantly reduced MC5R expression on the cell membrane surface. Transcriptome and qPCR data showed that both MRAP1 and MC5R were highly expressed in chicken liver. Additionally, we observed that ACTH might increase hepatic glucose production and decrease lipogenesis in primary hepatocytes, and dose-dependently downregulated the expression levels of ELOVL6 and THRSPA genes. These findings indicated that ACTH may act directly on hepatocytes to regulate glucolipid metabolism, which will help to understand the function of MC5R in avian.